2019
DOI: 10.1016/j.jallcom.2019.06.101
|View full text |Cite
|
Sign up to set email alerts
|

Facile mechanochemical synthesis of non-stoichiometric silica-carbon composite for enhanced lithium storage properties

Abstract: Facile mechanochemical synthesis of non-stoichiometric silica-carbon composite for enhanced lithium storage properties,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…With the effect of the high‐speed motor driven grinder in ball milling, the particle size of Si can be significantly reduced and the distribution of Si in matrix is uniform, which make it easier for Li + and interfacial charge to transport. Ultimately, better performance such as enhanced capacity and high capacity retention rate are obtained [21,41,54,65–68] . Combining with etching, ball mill method can also be used to prepare porous Si‐based anode materials.…”
Section: Synthesis Methods Of Silicon/carbon Anodesmentioning
confidence: 99%
See 1 more Smart Citation
“…With the effect of the high‐speed motor driven grinder in ball milling, the particle size of Si can be significantly reduced and the distribution of Si in matrix is uniform, which make it easier for Li + and interfacial charge to transport. Ultimately, better performance such as enhanced capacity and high capacity retention rate are obtained [21,41,54,65–68] . Combining with etching, ball mill method can also be used to prepare porous Si‐based anode materials.…”
Section: Synthesis Methods Of Silicon/carbon Anodesmentioning
confidence: 99%
“…Ultimately, better performance such as enhanced capacity and high capacity retention rate are obtained. [21,41,54,[65][66][67][68] Combining with etching, ball mill method can also be used to prepare porous Si-based anode materials. Researchers found that the problems of acid consumption and Si yield can be effectively solved by simply changing the sequence of the ball-milling and acid etching.…”
Section: Mechanical Millingmentioning
confidence: 99%
“…The mechanochemical method, also known as mechanical alloying, is a convenient solid-state processing technique in which the precursor powders are exposed to repeated welding, fracturing, and re-welding in a high energy ball mill. The method has been developed in the 1970s for the fabrication of nickel- and iron-base superalloys for applications in the aerospace industry [ 32 , 33 ] and is nowadays widely used in the processing of advanced materials like alloys [ 34 ], bimetallic nanocatalysts [ 35 ], oxide materials [ 36 , 37 ], carbon-based materials [ 38 , 39 , 40 ], etc. The first reports of mechanochemical synthesis of metal chalcogenides date back to the 1990s, and since then, a number of nanosized sulfides, selenides, and tellurides have been prepared using this method.…”
Section: Introductionmentioning
confidence: 99%
“…Abbreviations of the vocabulary. References [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ] are cited in the Supplementary Materials.…”
mentioning
confidence: 99%